Technical and Financial Analysis of Floating Lift Net Business in Tulehu Village, Central Maluku Regency - Bawole, Dionisius; Ruban, Angela; Apituley, Yolanda (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Uncertainty of sustainability is a common problem in the fisheries business due to the nature of the fishes, which are seasonal and highly perishable. Therefore, financial analysis of this kind of business is essential to maintain its sustainability. Many small-scale fishing businesses requires an organized financial record keeping. This research is aimed at (1). Analyze the technical conditions of the floating lift net business in Tulehu Village, Central Maluku Regency, and (2) Analyze the financial aspects of the floating lift net business in Tulehu Village, Central Maluku Regency. The results show that the floating lift net in Tulehu Village measured 18m x 20m, with the construction parts consisting of a balancer, lift net house, support poles, net rollers, and anchor rollers, while the parts of the additional equipment which consist of nets, lighting devices, boats, and transport machines as well as scoops. The average number of fishing activities for floating lift nets in non-fishing seasons is 55 trips, while in the fishing season, it is 138 trips, with different fishing areas depending on the season. Based on the investment assessment criteria, the average R/C calculation value is 3.4, the average PP value is 3.26, and the average ROI value is 34.87%. The floating lift net business at the research location is financially feasible to develop.